Tuning of Precursor Composition and Formation Pathway of Kesterite Absorbers Using an In‐Process Composition Shift: A Path toward Higher Efficiencies?. Issue 8 (11th July 2021) - Nowak, David; Taskesen, Teoman; Pareek, Devendra; Pfeiffelmann, Timo; Mikolajczak, Ulf; Gütay, Levent
Abstract : This work reports a growth process for tuning the formation pathway and final composition of kesterite Cu2 ZnSnSe4 (CZTSe) thin film absorbers. By adjusting the as‐grown composition of the precursor, the kesterite formation can be started in a Cu‐rich, stoichiometric, or Cu‐poor environment. During the high‐temperature stage of the annealing process, incorporation or loss of SnSe2– x vapor at the layer is used to achieve an in‐process composition shift during further kesterite growth (e.g., Cu‐rich to Cu‐poor/Cu‐poor toward Cu‐rich). This approach partially decouples the composition of the as‐grown precursor and the final absorber, which, thus, can be tuned independently. The film growth, specifically the composition shift during the process, is tracked by interruption experiments. The influence of the starting composition of the precursor and the resulting absorber composition on the optoelectronic properties and device performance of the final solar cells is discussed. The results show a refined composition region for reduced Urbach tailing and lower V OC deficit. The best solar cells show efficiencies > 11% and a V OC deficit < 320 mV (relative to the Shockley–Queisser limit). Abstract : Sn content varying precursors are annealed with a composition shift in terms of Sn content, facilitated by vapor phase incorporation/reduction of Sn in the kesterite film, allowing to control the amount and direction of the composition shift (Cu‐rich ↔ Cu‐poor) during absorber formation. The starting and final compositions influence the resulting solar cell properties independently.